2023
DOI: 10.3389/fmars.2023.1134844
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gonad reproductive state using non-lethal ultrasonography in endangered black (Haliotis cracherodii) and white abalone (H. sorenseni)

Abstract: IntroductionBlack (H. cracherodii) and white abalone (H. sorenseni) are federally listed as endangered species in the United States. Conservation efforts include captive breeding programs; however, determination of the reproductive state of individual abalone is notoriously difficult using traditional visual assessments. Ultrasonography is a well-recognized technology used to assess gonad reproductive condition accurately and nonlethally in cultured and wild fish, and more recently cultured red abalone (H. ruf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…As part of a broader conservation effort to mitigate the impact of climate change on endangered abalone populations (National Marine Fisheries Service, 2008, we sought to investigate the direct and indirect effects of temperature on dulse and juvenile abalone physiology respectively. Our results contribute to a comprehensive exploration of the effects of ocean warming on abalone physiology, including adult reproductive health, with consequences for hatchery management and juvenile abalone recruitment (Boles et al, 2022(Boles et al, , 2023. Concurrent efforts by Neylan et al (2023), revealed slower growth, delays in fecundity, and decreased gonad tissue thickness on adult abalone when exposed to elevated ocean acidification conditions at 14°C.…”
Section: Indirect Effects Of Temperature On Juvenile Abalone Growthmentioning
confidence: 67%
“…As part of a broader conservation effort to mitigate the impact of climate change on endangered abalone populations (National Marine Fisheries Service, 2008, we sought to investigate the direct and indirect effects of temperature on dulse and juvenile abalone physiology respectively. Our results contribute to a comprehensive exploration of the effects of ocean warming on abalone physiology, including adult reproductive health, with consequences for hatchery management and juvenile abalone recruitment (Boles et al, 2022(Boles et al, , 2023. Concurrent efforts by Neylan et al (2023), revealed slower growth, delays in fecundity, and decreased gonad tissue thickness on adult abalone when exposed to elevated ocean acidification conditions at 14°C.…”
Section: Indirect Effects Of Temperature On Juvenile Abalone Growthmentioning
confidence: 67%